H∞ Control for Fuzzy Switched Cyber-Physical Systems Subject to DoS Attacks - Yang, Dong; Xin, Aoting; Zong, Guangdeng; Xie, Jing (IEEE transactions on fuzzy systems, 2024)
This paper studies the H_∞ control problem for fuzzy switched cyber-physical systems (FSCPSs) subject to denial-of-service (DoS) attacks. An observer state-dependent switching signal is designed using the multiple Lyapunov function technology under the unavailable system states. When DoS attacks occur, the information transmission involving the sensor and controller data is corrupted. Under the designed switching signal, the subsystem with the lowest energy is selected in both the DoS sleeping interval and the DoS activated interval. First, a switching technique is introduced to deal with a DoS attack behavior. The H_∞ control problem of the considered FSCPS is divided into two cases for handling: the presence and absence of DoS attacks. Then, a fuzzy switching observer and an observer-based fuzzy switching controller are proposed to guarantee the solvability of the H_∞ control problem for FSCPSs with DoS attacks. Finally, a simulation example demonstrates the effectiveness and usefulness of the proposed fuzzy switching control strategy for FSCPSs subject to DoS attacks.